IMPLEMENTASI ADIWIYATA (SEKOLAH PEDULI LINGKUNGAN) DI SMA NEGERI 1 PEKANBARU - Eka Suryani; Isjoni Isjoni; Murni Baheram (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2020)
This research aims to know the implementation of adiwiyata (school environment) in SMA Negeri 1 Pekanbaru. The method was used is the qualitative approach. Dotted defends on the findings of the research have been done, nestling be drawn the conclusion that it is in the planning stages of the program adiwiyata in SMA Negeri 1 Pekanbaru, the role of the principal, teachers, and the school committee is very important. A good cooperation in the preparation of the programs and activities that support program adiwiyata, this is what makes the planning to be mature and be able to carried out well in school. In the stage of implementation, the good cooperation of the principal as a leader, teacher and administrative activities in the program as a constructor of adiwiyata, the student as a daily executor and the committee as a supporting factor and the trustees made programme adiwiyata in SMA Negeri 1 Pekanbaru were carried out to its full potential and achive the desired objectives. See from the result of the implementation of adiwiyata programme in SMA Negeri 1 Pekanbaru, reflected that the successful implementation of the program has achieved the desired goals. From 2009 until 2016 always showed an increase to a better direction, program adiwiyata in SMA Negeri 1 Pekanbaru became a model for other schools and should afford to become environmentally independent school.